Alterations of Brain Metabolites in Adults With HIV: A Systematic Meta-analysis of Magnetic Resonance Spectroscopy Studies. (14th September 2021) - Dahmani, Sophia; Kaliss, Nicholas; VanMeter, John W.; Moore, David J.; Ellis, Ronald J.; Jiang, Xiong
Abstract : Objective: A meta-analysis of proton magnetic resonance spectroscopy studies to investigate alterations in brain metabolites in people with HIV (PWH), the relationship between metabolite alterations and combination antiretroviral therapy (cART), and the relationship between metabolite alterations and cognitive impairment. Methods: The PubMed database was searched for studies published from 1997 to 2020. Twenty-seven studies were identified, which included 1255 PWH and 633 controls. Four metabolites (N-acetyl aspartate [NAA], myo-inositol [mI], choline [Cho], and glutamatergic metabolites [Glx]) from 5 brain regions (basal ganglia [BG], frontal gray and white matter [FGM and FWM], and parietal gray and white matter [PGM and PWM]) were pooled separately using random-effects meta-analysis. Results: During early HIV infection, metabolite alterations were largely limited to the BG, including Cho elevation, a marker of inflammation. cART led to global mI and Cho normalization (i.e., less elevations), but improvement in NAA was negligible. In chronic PWH on cART, there were consistent NAA reductions across brain regions, along with Cho and mI elevations in the FWM and BG, and Glx elevations in the FWM. Cognitive impairment was associated with NAA reduction and to a lesser degree mI elevation. Conclusions: The BG are the primary region affected during early infection. cART is successful in partially controlling neuroinflammation (global mI and Cho normalization). However, neuronal dysfunction (NAA reductions) and neuroinflammation (mI and Cho elevations) persist and contribute to cognitive impairment in chronic PWH. Novel compounds targeting NAA signal pathways, along with better neuroinflammation control, may help to reduce cognitive impairment in PWH.